Colloid goitre in submental ectopic thyroid: a rare entity posing a diagnostic and therapeutic challenge - Sarkar, Santanu; Panja, Soumyajyoti; Mandal, Kaushik; Kumar, Sandeep (International Surgery Journal, 2016)
Ectopic thyroid is a rare entity in clinical practice. It results from defects at early stages of thyroid gland embryogenesis, during its passage from the base of the tongue to its final pre-tracheal position, anterolateral to second, third, and fourth tracheal rings. It is usually found along the course of the thyroglossal duct or laterally in the neck, also in distant places such as the mediastinum or very rarely in the sub-diaphragmatic organs. In our case, an 18-year old girl presented with a sub-mental swelling. There are various differentials for such swelling. A careful history, scrupulous clinical examination and investigations comprising ultrasonography of neck, MRI scan, Tc-99m pertechnetate thyroid scan and Fine needle aspiration cytology (FNAC) from the swelling revealed that it was a case of colloid goitre in the ectopic sub-mental thyroid and there was no thyroid tissue in its normal anatomic location. We initially treated the patient with supplemental levothyroxine trial for 6-months followed by surgical excision. We report this case as it is a rare phenomenon and also because diagnostic and therapeutic dilemma exists in its management.